A model for exploring modernist novellas in training pre-service secondary school teachers - Башкирова, Ольга (Київський національний університет імені Тараса Шевченка, 2024)
Introduction. Teaching methodology experts have long recognised the significance of applying literary terminology in analysing fiction texts in schools. Students often face difficulties using terms due to the mechanical approach to learning these concepts and the lack of proper systematisation. There is a pressing need for education majors to systematically and consciously incorporate the main categories of literary theory into classroom practice. A crucial aspect of their professional training involves mastering a coherent and logical framework for analysing literary works, particularly modernist novellas. Research objectives. The aim of this article is to establish a model for practically implementing a technology for analysing modernist novellas through a structural and stylistic approach. The analysis is based on Volodymyr Vynnychenko's novella, "The Moment." This particular work was chosen to test the analytical model due to the significant challenges that modernist literature presents in educational settings. Methodology. The educational model for analysing modernist novellas is based on structural and stylistic approaches. The purpose of this model is to identify the aesthetic dominant of the author's work while considering its correlation with the leading trends of the epoch and the literary movement to which the author belongs. To support this, methods of analysis and synthesis are utilised to uphold the principle of the integrity of a literary work. Comparative and typological methods highlight the artistic specificity of short fiction genres. Comparative and historical methods allow for comparing the worldview and aesthetic foundations of both realist and modernist writing. For the practical implementation of this analytical model, the leading instructional methods include heuristic conversations and posing problematic questions. Results and discussion. The model under discussion consists of several key components. It involves ideological and aesthetic elements of an individual author's style, specific artistic techniques employed by the author, the genre features of a work, and the characteristics of the artistic movement to which the writer belongs. The model is based on several guiding principles, including the recognition that a work of fiction is the primary component of the literary process and that the work must be viewed as an aesthetic whole formed by the interaction of all its elements. The anticipated outcomes of using this model in school education include a thoughtful and informed use of literary studies terminology, an appreciation for the significance of individual works of art in literary progress, and a comprehensive understanding of the multilevel nature of literary works.

У статті представлено модель аналізу літературного твору, зокрема модерністської новели, що варто запропонувати студентам освітніх спеціальностей під час університетської підготовки до роботи в середній школі. На прикладі новели Володимира Винниченка "Момент" продемонстровано модель вивчення зразків малої прози межі XIX–XX ст. на шкільних уроках української літератури. Описано схему аналізу новели, яка враховує поетологічні особливості твору, зумовлені загальними естетичним тенденціями доби й специфікою індивідуально-авторської картини світу. Спеціальну увагу приділено проблемам літературної генерики, які не охоплені шкільною програмою, проте необхідні для майбутнього вчителя: визначенню жанрових меж новели, її структурним типам, особливостям композиції. Окреслено можливі шляхи актуалізації теоретико-літературних понять (пейзаж, художня деталь, ідея) під час вивчення новели на уроках української літератури. Обґрунтовано необхідність цілісного аналізу твору, шо враховує взаємозв'язок усіх його художніх елементів, описано способи застосування моделі у шкільній лекції. Представлена навчальна модель спирається на визнання первинності художнього твору як головного складника літературного процесу, що визначає естетичні тенденції певної культурної епохи.
Модель аналізу модерністської новели у процесі підготовки студентів освітніх спеціальностей до викладання в середній школі
Keywords: модель аналізу літературного твору; студенти освітніх спеціальностей; модерністська новела; художній стиль; художній напрям; жанр; a model for analysing a literary work; education major students; modernist novella; artistic style; artistic movement; genre